Prognostic Nutritional Index (PNI) in Patients With Breast Cancer Treated With Neoadjuvant Chemotherapy as a Useful Prognostic Indicator - Chen, Li; Bai, Ping; Kong, Xiangyi; Huang, Shaolong; Wang, Zhongzhao; Wang, Xiangyu; Fang, Yi; Wang, Jing (Frontiers in Cell and Developmental Biology, 2021)
Prognostic nutritional index (PNI), calculated as serum ALB (g/L) + 5 × total lymphocyte count (109/L), is initially used to evaluate nutritional status in patients undergoing surgery and may evaluate the therapeutic effects and predict the survival of various solid tumors. The present study is aimed to evaluate the potential prognostic significance of PNI in breast cancer patients received neoadjuvant chemotherapy. A total of 785 breast cancer patients treated with neoadjuvant chemotherapy were enrolled in this retrospective study. The optimal cutoff value of PNI by receiver operating characteristic curve stratified patients into low PNI group (＜51) and high PNI group (≥51). The results indicated that PNI had prognostic significance by optimal cutoff value of 51 on DFS and OS in univariate and multivariate Cox regression survival analyses. The breast cancer patients with high PNI value had longer DFS and OS than those with low PNI value (47.64 vs 36.60 months, P＜0.0001, HR: 0.264, 95% CI: 0.160-0.435; 73.61 vs 64.97 months, P＜0.0001, HR: 0.319, 95% CI: 0.207-0.491, respectively). Furthermore, the results indicated that patients with high PNI had longer DFS and OS than those with low PNI in early-stage and advanced breast cancer, especially in advanced breast cancer. And the mean DFS and OS time for breast cancer patients with high PNI by the log-rank test were longer than in those with low PNI in different molecular subtypes. Moreover, the mean DFS and OS time in patients with high PNI by the log-rank test were longer than in those patients with low PNI without or with lymph vessel invasion. The common toxicities after neoadjuvant chemotherapy were hematologic and gastrointestinal reaction, and the PNI had no significance on toxicities of all enrolled patients, excepted in anemia, leukopenia and myelosuppression. Pretreatment PNI with the advantage of convenient, non-invasive and reproducible was a useful prognostic indicator for breast cancer patients received neoadjuvant chemotherapy, and is a promising biomarker for breast cancer on treatment strategy decisions.